Half-Earth or Whole-Earth? Green or transformative recovery? Where are the voices from the Global South? - Kothari, Ashish (Oryx, 2021)
If conservationists of the Global North are serious about saving the Earth, and I would like to believe they are, then they need to listen carefully to people such as Nemonte Nenquimo of the Waorani Indigenous people in the Amazon (‘This is my message to the western world—your civilization is killing life on Earth’; Nenquimo, 2020), and to those communities who have told the advocates of nature-based solutions that ‘our nature is not your solution’ (Global Forest Coalition, 2020b). Global networks comprising Indigenous peoples and local community organizations and civil society groups, such as the Indigenous Peoples’ & Community Conserved Territories & Areas Consortium (ICCA, 2021), and the Global Forest Coalition, have shown how community-led conservation approaches, especially if there is a supportive policy context such as recognition of tenure and the right of self-determination, can work. Most Half-Earth protagonists live in conditions radically altered by industrialization: they cannot possibly imagine living one's whole life as an artisanal hunter, gatherer, fisher, farmer or forest-dweller whose livelihood, culture, entertainment, language, food, relationships and emotions are conditioned by everyday interactions with the natural world.